Towards an adult hearing screening procedure - Marc Jan-Willem Lammers; Chris Raine; Griet Mertens; Vincent van Rompaey; Rudolf Hagen; Anja Kurz; Piotr Henryk Skarzynski; Artur Lorens; Jane Opie; Patrick D’Haese; Peter Grasso; Luis Lassaletta; et al. (Brazilian Journal of Otorhinolaryngology, 2025)
Objective: The first aim was to develop a simple, yet effective adult hearing screening protocol, based on the existing World Health Organization recommendations. Secondary aim was to gain insight in the possibilities and potential obstacles for implementation of national adult hearing screening programs across the globe. Methods: An expert working group was formed with 14 experts from six countries. Based on their recommendations a HEARRING screening protocol was devised and shared with all HEARRING group members. A survey was sent out to 62 clinicians from 22 countries to hear their considerations and the potential challenges they expect for the introduction of national adult hearing screening programs. Results: The proposed adult hearing screening protocol is made as simple and least time consuming as possible. The tablet-based screening tool consists of two red flag questions, followed by the Hearing Handicap Inventory for the Elderly Screening (HHIE-S) questionnaire and the Digits-in-Noise test, and is developed to be implemented in the primary care setting. The results of our survey indicate that most participants deem a national adult hearing screening to be cost-effective, but the major concerns regarding costs and funding, and infrastructure have to be discussed. Conclusion: The HEARRING screening protocol is developed to assist clinicians and policy makers in their efforts to initiate effective local and national adult hearing screening programs.